The Snow merchant - Gayton, Sam.; Riddell, Chris (London : Andersen Press, 2014)
Lettie Peppercorn lives in a house on stilts near the wind-swept coast of Albion. Nothing incredible has ever happened to her, until one winter's night, when the night the Snow Merchant comes. He claims to be an alchemist - the greatest that ever lived - and in his suitcase, he carries his newest invention: snow.
5-8.